The goals of community-based corrections: An analysis of state legal codes - Johnson, W. Wesley (American journal of criminal justice, 1994)
The increased reliance on community-based correctional programs has been influenced by rising offender populations and the need for states to lessen prison crowding. The ability of community-based corrections to provide rehabilitation, punishment, reintegration, and counseling services has been an issue among both researchers and administrators. Some researchers have asserted that community-based correctional programs have multiple or competing functions. This study examines 1992 legal codes for all fifty states to determine the legally prescribed goals as mandated by state legislatures. The findings suggest that rehabilitation is the primary legislatively mandated goal, and that most states have multiple purposes for handling offenders in the community. Suggestions for future research in the area of community-based corrections goals are made.